Autonomic Nervous System Dysfunction in Primary Sjögren’s Syndrome - Davies, Kristen; Ng, Wan-Fai (Frontiers in Immunology, 2021)
Primary Sjögren’s syndrome (pSS) is an autoimmune disease that primarily affects the exocrine glands, but can also affect other organs, including the nervous system. Many studies have reported evidence of autonomic nervous system (ANS) dysfunction in pSS which may contribute to a wide range of symptoms and functional burden. Symptoms of ANS dysfunction are common and widespread among patients with pSS and are associated with other features of the disease, particularly fatigue. Accumulating data on the inter-relationship between the ANS and the immune system via the vagus nerve have been reported. Vagus nerve stimulation (VNS) has also been associated with improvement in fatigue in patients with pSS. Taken together, these data suggest that the ANS may be a potential treatment target for pSS, in particular those with fatigue being a predominant symptom. Future research to dissect the link between the ANS, immune dysregulation and clinical manifestations in pSS and to evaluate the potential of VNS as a therapy for pSS is warranted.